IMAGE CHARACTERISTICS OF IT ENTERPRISES: FEATURES OF DEVELOPMENT IN THE CONDITIONS OF INFORMATION ECONOMY AND INFORMATION SOCIETY - Храпкіна, Валентина; Матвієнко, Олена (SWorldJournal, 2024)
The article is devoted to the current issues of the development of the IT sphere, its leadership positions in the global information and communication space. The conditions and basic processes of forming the image of IT enterprises in the conditions of t